2018
DOI: 10.1002/cppb.20065
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Agrobacterium‐Mediated Transformation of Potato (Solanum tuberosum) and Production of Transgenic Microtubers

Abstract: The following method enables the rapid production of transgenic potato plants and microtubers for gene validation and expression, or promoter studies. The method is highly efficient, with reproducible transformation efficiencies of at least 50% to 60% with potato cv. Desiree, and can produce transgenic microtubers within 6 months of initiation of the experiment. Microtubers are produced in the absence of hormones, giving an in vitro gene testing system broadly analogous to the natural state. © 2018 by John Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…The implementation of a regeneration procedure for ‘Yagana-INIA’ was based on previous descriptions in ‘Désirée’ [ 23 ]. After adjustments, we observed that the ‘Yagana-INIA’ explants responded to the respective culture media with a progressive delay as development stages advanced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of a regeneration procedure for ‘Yagana-INIA’ was based on previous descriptions in ‘Désirée’ [ 23 ]. After adjustments, we observed that the ‘Yagana-INIA’ explants responded to the respective culture media with a progressive delay as development stages advanced.…”
Section: Resultsmentioning
confidence: 99%
“…Positive clones were purified using the Zymo Miniprep Kit (Zymo Research) and sequenced (Macrogen Inc.) to verify a correct assembly, also using the gmv-CI-Fw/gmv-CI-Rv primer pair. pGEF-X clones were electroporated into electrocompetent Agrobacterium tumefaciens strain EHA105 as described above and used to transform leaf explants of ‘Yagana-INIA’, according to the previously described procedure [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and the GA 3 also had different concentration in different species. The results of others research also indicated that the hormone ratio required for different genotypes of potato to differentiate into shoots was different, and the differentiation efficiency was similarly different [21][22][23][24][25].…”
Section: Selection Of Shoots Induction Medium For Callusmentioning
confidence: 99%
“…Potato is primitively domesticated and consumed in North America, Europe, former USSR nations, and now a large number of cultivations are carried out in South Africa, Asia, and South America. This makes potato the world's fourth most imperative crop in terms of production (Hong et al, 2017;Craze et al, 2018). It has been reported that worldwide potato production was 388,190,674 tonnes with the area cultivated on 19,302,642 hectares (FAOSTAT, 2017).…”
Section: Introductionmentioning
confidence: 99%